Integration of Hospital Service Quality Dimensions in Enhancing Patient Satisfaction and Trust - Fanytha Libra Karmila; Habibi Habibi; I Gede Willy Karya Mahardika; I Gusti Made Dika Wahyu Krisnantara; Jovita Liman; A. Rohendi (CV. Civiliza Publishing, 2026)
The objective of this research is to analyze in depth how the integration of various dimensions of hospital service quality plays a role in building satisfaction and strengthening patient trust through a qualitative approach. This study employs a descriptive research type to capture service realities objectively through literature review data collection techniques from various relevant textbooks and scientific journals. Data analysis processes are carried out systematically through stages of data reduction, narrative data display, and conclusion drawing to provide a complete picture of the phenomenon being studied. Research results indicate that empathy and responsiveness dimensions become the most dominant factors in determining patient trust levels because these two aspects touch the psychological side of humans who are in a vulnerable condition. Hospitals perform integration through standardization of procedures across all units, improvement of physical facilities, and the use of information technology to accelerate administrative processes without losing the staff's personal touch. Main constraints faced by management include limited numbers of health workers and differences in perception regarding quality between medical staff and patients. Strategies to overcome these obstacles are carried out through regular human resource training, strengthening patient-oriented service culture, and continuous evaluation based on direct feedback from the community.